De-Westernization and Cosmopolitan Media Studies - Waisbord, Silvio (Internationalizing "International Communication", 2015)
The call for the “De-Westernization” (Curran & Park, 2000) of media studies hasattracted much attention in recent years. It is generally associated with the need to giveserious considerations to media systems outside the West. This paper critically reviewsthe meaning of “de-Westernization,” and argues that the main challenge is not simply to broaden the geographic scope by considering cases from the global South. The inclusionof non-Western cases could lead to the consolidation of “area studies”, a balkanizedresearch that may not contribute to a common set of questions and unifying theories.Instead, it is necessary to approach de-Westernization in order to promote cosmopolitanscholarship, an analytical approach that is open to the globalization of problems andacademic production. Rather than being constrained by geographical divisions, de-Westernization should help to expand analytical perspectives and brings theoretical andcomparative questions to the forefront of media studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé